A Composição por Fórmula de Karlheinz Stockhausen: processos de projeção da Superfórmula de Licht em Kathinkas Gesang als Luzifers Requiem - Miranda, Paulo Agenor (2015)
This dissertation is focused on the study of the formula composition concept, by Karlheinz Stockhausen. The concept refers to the compositional principle developed since early 1970s that outlines the compositional approach taken by Stockhausen in his following works. The composer begins with a compositional plan - the so-called formulas - and applies several processes to them (transformation, expansion, compression or, in his own words, the projection of this musical core) in order to create the macro- and micro-structural levels of his works. With the aim of studying the formula projection from an analytical point of view, the work Kathinkas Gesang als Luzifers Requiem is taken in order to reveal the projection of the Superformula of Licht in the instrumental or electronic components of the work - therefore explaining the generative and compositional processes that are specific to Stockhausen’s compositional approach. The theoretical and methodological choices taken in this study enabled us to crossover musical and non-musical aspects that converge to Stockhausen’s formula composition. In these sense, this study refers, on one hand, to religious, symbolic and biographical aspects related to Stockhausen’s cosmovision and, on the other hand to technical and musical aspects related to the projection of the Superformula in the composition of the Licht cycle. All those aspects, in turn, converge among themselves and intermodulate, highlighting the poetics of Kathinkas Gesang. This ultimately reveals the poetic development of the formula composition principle. As a conclusion, it is important to note the high level of material coherence established between the Luzifer formula and all formal instances of Kathinkas Gesang, since its macro-structure, the elaboration of its 29 sections, up to to its musical surface which is manifested by its sound gestures.